Secondary Traumatic Stress and Burnout Among Refugee Resettlement Workers: The Role of Coping and Emotional Intelligence. Issue 2 (18th April 2018) - Akinsulure‐Smith, Adeyinka M.; Espinosa, Adriana; Chu, Tracy; Hallock, Ryan
Abstract: To promote a better understanding of the impact of refugee resettlement work on refugee resettlement workers, this study examined the prevalence rates of deleterious mental health and occupational outcomes, such as secondary traumatic stress and burnout, among a sample of 210 refugee resettlement workers at six refugee resettlement agencies in the United States. The study also explored coping mechanisms used by service providers to manage work‐related stress and the influence of such strategies and emotional intelligence on secondary traumatic stress and burnout. Our findings show that certain coping strategies, including self‐distraction, humor, venting, substance use, behavioral disengagement, and self‐blame, were strongly related to deleterious outcomes, βs = .18 to .38, p s = .023 to < .001. Emotional intelligence was a negative correlate for all outcomes, βs = −.25 to −.30, p s < .001, above and beyond the effects of trauma, coping styles, job, and demographic characteristics. These findings have potential implications for clinical training and organizational policy regarding refugee mental health.